2002
DOI: 10.1021/jp020431z
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation Density Functional Theory for Density Profile of A Nonuniform and Uniform Hard Core Attractive Yukawa Model Fluid

Abstract: The nonuniform first-order direct correlation function (DCF) for a hard-core attractive Yukawa model fluid (HCAYMF) was expanded around bulk density and truncated at the lowest order. The truncation was made formally exact by applying the functional counterpart of Lagrangian theorem of the differential calculus to the functional expansion. To calculate the density profile of a nonuniform HCAYMF, the uniform secondorder DCF from the mean spherical approximation for HCAYMF was employed; the resulting density fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 45 publications
(44 reference statements)
1
22
0
Order By: Relevance
“…If we fix a sphere, then the external potential produced by the fixed sphere is given by If the density profile of other spheres around the fixed particle is calculated from the DFT, the radial distribution function g(r) can be obtained through Equation 23 has been applied to attractive and repulsive HCY fluids. Figure 10 depicts the predicted radial distribution functions for the attractive HCY fluid at reduced temperature T* ) 2.0 and reduced densities 25, we found that the present DFT gives a more accurate radial distribution function than Zhou's perturbation DFT 25 does. Furthermore, our DFT is simpler in calculation than that of Zhou because we avoid the determination of the parameter from the bulk pressure.…”
Section: Resultsmentioning
confidence: 80%
“…If we fix a sphere, then the external potential produced by the fixed sphere is given by If the density profile of other spheres around the fixed particle is calculated from the DFT, the radial distribution function g(r) can be obtained through Equation 23 has been applied to attractive and repulsive HCY fluids. Figure 10 depicts the predicted radial distribution functions for the attractive HCY fluid at reduced temperature T* ) 2.0 and reduced densities 25, we found that the present DFT gives a more accurate radial distribution function than Zhou's perturbation DFT 25 does. Furthermore, our DFT is simpler in calculation than that of Zhou because we avoid the determination of the parameter from the bulk pressure.…”
Section: Resultsmentioning
confidence: 80%
“…It may be noted that this form of the weighted density has also been used by Zhou. 31,32 Clearly in the homogeneous limit of F(r) f F 0 , F j(r) reaches the bulk density F 0 irrespective of the value of the parameter λ. The final equation for the first-order DCF c (1) -(r;[F]) of eq 5 is thus given by…”
Section: Density Functional Theory Of An Inhomogeneous Fluidmentioning
confidence: 98%
“…and n α are the weighted densities (or fundamental measures). For the attraction term, some non-mean-field methods including the weighted density approximation [35][36][37] and quadratic density expansion 38,39 have been shown to be more accurate for simple fluids and have been successfully applied to several inhomogeneous systems such as square-well fluids, 40 Lennard-Jones fluids, 41 Yukawa potentials, 42,43 and Sutherland fluids. 44 However, these methods have not yet been extended to the polymer brush system.…”
Section: Theorymentioning
confidence: 99%